TEOLOGI DIGITAL DAN RELEVANSI MISI GEREJA DI ERA VIRTUAL: STUDI KRITIS EVANGELISASI ONLINE DI KALANGAN GENERASI MILENIAL DAN GEN Z - Bambang Sriyanto; Aji Suseno (Manna Rafflesia, 2025)
The sophistication of digital-based technology and communication has shaped a new culture that fundamentally changes the way humans relate to and understand reality, including in their spiritual lives. The Church, as a community of faith, is challenged to redefine its mission of proclaiming the Gospel to align with the dynamic and complex communication patterns of the digital generation. Unfortunately, many online evangelisation practices remain technical in nature and lack deep theological reflection. Millennials and Gen Z, as digital natives, show an interest in spirituality but feel disconnected from church institutions perceived as irrelevant. This study aims to develop a theology of mission to address the dynamics of digital evangelisation among these younger generations. Through a qualitative approach based on literature review, the conclusion of this study states that digital theology becomes a new foundation for relevant Gospel proclamation in the virtual era, especially in reaching Millennials and Gen Z who live in a digital culture. Online evangelism practices require the development of contextual, ethical, and authentic message-based digital missiology. Therefore, the church needs to reformulate its mission theology as a form of incarnational, dialogical, and transformative witness in the midst of an ever-evolving virtual world.